Simulasi Potensi Banjir Sungai Way Balau Menggunakan HEC-RAS dan Data Curah Hujan Satelit - Dea Septa Ananda; Alfath Zain; Destiana Safitri (Jurnal Konstruksi, 2025)
This study aims to simulate the flood potential of the Way Balau River, Bandar Lampung City, using rainfall data from the GPM-IMERG satellite and HEC-RAS software. The analysis uses a log-normal distribution for rainfall, a rational method for discharge calculation, and water level simulation is performed at STA. 301. The results show that a 0.5 m high embankment on the left side is capable of withstanding a 5-year return period discharge, but in the 25, 50, and 100-year return periods, there is overflow on the right side with water heights of 0.16 m, 0.25 m, and 0.33 m, respectively. This study recommends increasing the capacity of the embankment on the right side of the river to mitigate the risk of long-term flooding.